Numerical and Experimental Investigation on Post-buckling ‎Behavior of Stiffened Cylindrical Shells with Cutout subject to ‎Uniform Axial Compression - Amir Shahani; Faraz Kiarasi (Journal of applied and computational mechanics, 2023)
In this paper, post buckling behavior of thin steel and aluminum cylindrical shells with rectangular cutouts under axial loading was studied experimentally and also using the finite element method. Riks method is used for analyzing the cylindrical shells. The effect of longitudinal and circumferential stiffeners (ribs and stringer) was studied on the buckling load and the post buckling behavior as the stiffeners used individually and in combination with each other. It was shown that by adding stringer, the buckling load improves and the rib has a positive effect on the post buckling behavior of the structure. Some tests were performed by ZwickRoell tensile/compression testing machine and it was carried out for both types of steel and aluminum shells with and without stiffeners. Comparing the experimental results with the FEA results shows good agreement. Nonlinear analysis of cylindrical steel and aluminum shells with cutout have demonstrated that, in some cases, a local buckling called snap-back can be seen in the load-displacement path. Snap-back which is a decrease in the amount of both load and displacement indicates this local buckling. This phenomenon is because of appearing mode shapes sequentially during the numerical buckling analysis of shells. Although these local buckling happened, the structure is still endured the higher loads.